Deficiency of H3K79 Histone Methyltransferase Dot1-like Protein (DOT1L) Inhibits Cell Proliferation - Kim, Wootae (American Society for Biochemistry and Molecular Biology, 2012)
Dot1-like protein (DOT1L) is an evolutionarily conserved histone methyltransferase that methylates lysine 79 of histone H3 (H3K79). Mammalian DOT1L participates in the regulation of transcription, development, erythropoiesis, differentiation, and proliferation of normal cells. However, the role of DOT1L in cancer cell proliferation has not been fully elucidated. DOT1L siRNA-transfected A549 or NCI-H1299 lung cancer cells displayed a nonproliferating multinucleated phenotype. DOT1L-deficient cells also showed abnormal mitotic spindle formation and centrosome number, suggesting that DOT1L deficiency leads to chromosomal missegregation. This chromosomal instability in DOT1L-deficient cells led to cell cycle arrest at the G(1) phase and induced senescence as determined by enhanced activity of senescence-associated β-galactosidase activity. Meanwhile, overexpression of a catalytically active DOT1L, not an inactive mutant, restored DOT1L siRNA-induced phenotypes. Overall, these data imply that down-regulation of DOT1L-mediated H3K79 methylation disturbs proliferation of human cells. In addition, although H3K79 methylation is down-regulated in aged tissues, it is up-regulated in lung cancer cell lines and tumor tissues of lung cancer patients. Therefore, H3K79 methylation is a critical histone modification that regulates cell proliferation and would be a novel histone mark for aging and cancer.